Black book - Beker, Jeroen; Berkel, Christian, 1957-; Blok, Peter; De Vries, Dolf; Hilte, Teun; Hoffman, Thom; Huisman, Michiel; Kobus, Waldemar; Koch, Sebastian, 1962-; Lint, Derek de, 1950-; Maltha, San Fu; Meurer, Jens; et al. (Tartan Video, 2007)
A young Jewish girl hides out from the Nazi's during World War II in The Netherlands. After her hiding place is literally blown, she escapes with her rescuer, a young sailer. That same night, as she is hiding with the sailer, she is warned by the Dutch resistance that their hiding place has been located by the Germans. The next day they take off toward the liberated areas. That night the boat sails into a trap set by the Germans. Rachel escapes and joins the resistance. Under the false name Ellis de Vries she meets SS-hauptsturmführer Ludwig Muntze on a train smuggling weapons. She goes to his head quarters to meet him again and gain his trust. He soons falls for her and joins his office as a spy. But when someone within the resistance betrays her, she is now seen as an enemy betraying both sides. All that's left to do is run with the man she learned to love and find a way to prove her innocence by finding the real betrayer.